Joint autofocus and registration for video-SAR by using sub-aperture point cloud - Jun Shi; Yihang Zhou; Zhikun Xie; Xiaqing Yang; Wenxuan Guo; Fuwei Wu; Chengyuan Li; Xiaoling Zhang (International Journal of Applied Earth Observations and Geoinformation, 2023)
Due to the existence of antenna phase center (APC) error, drift occurs on the sequence of images acquired by video-SAR back projection (BP) algorithm with respect to a fixed coordinate system. Theoretical analysis shows that the drift is directly related to APC errors. Thus, we propose a novel joint autofocus and registration framework (JAR-PC) for video-SAR in this paper. By estimating the isometric transformation in the sub-aperture SAR image point cloud via the robust point matching network (RPM-Net), the low-order measurement error of the inertial navigation system (INS) is calibrated accurately. Applying the compensated APC trajectory to the BP algorithm, accurate registration and well-focused W-band video-SAR images are obtained. Experimental results show that JAR-PC can easily expand the aperture length from 3 s to 9 s without any visible defocusing, and coherently fuse multiple sub-aperture SAR images into a long-aperture SAR image. By combining the moving-target back projection (m-BP) algorithm with the shadow-tracking technique, JAR-PC can accurately project the SAR image to a geographical coordinate system with moving targets tracked, refocused and well-indicated.